Answer:
Explanation:
Hello,
We will prove it by induction.
Step 1 - for n=2
2!=2*1=2
2^2=4
and 2 < 4 so this is true for n=2
Step2 - We assume that this is true for k and we have to prove it for k+1.
Induction hypothesis is
![k!<k^k](https://img.qammunity.org/2021/formulas/mathematics/college/8eyejyetp5xkc20n1fn323talhk2l0kbq7.png)
![(k+1)!=(k+1)k!](https://img.qammunity.org/2021/formulas/mathematics/college/szfwzjp87o8xzbpu8u6h4oyjbqt7zeqi6d.png)
We use the induction hypothesis and we we can write that
![(k+1)!=(k+1)k!<(k+1)k^k<=(k+1)(k+1)^k=(k+1)^(k+1)\\\\\text{As }k <= k+1](https://img.qammunity.org/2021/formulas/mathematics/college/k71errmsm5nrcdivdv0lpapct1ome1o3x8.png)
so, we prove it for k+1
Step 3- conclusion
for n >= 2 we just proved that
![n!<n^n](https://img.qammunity.org/2021/formulas/mathematics/college/yyr24p4dbzeccptnrwud9i390913n80vo1.png)